The UTIP global inequality datasets: 1963-2008 - James K. Galbraith; Béatrice Halbach; Aleksandra Malinowska; Amin Shams; Wenjie Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper summarizes a comprehensive revision and update of UTIP's work on the inequality of pay and incomes around the world, from 1963 to 2008. The new UTIP-UNIDO (University of Texas Inequality Project-United Nations Industrial Development Organization) dataset of industrial pay inequality has 4,054 country-year observations for 167 countries, while the revised EHII (Estimated Household Income Inequality) dataset of estimated gross household income inequality has 3,872 observations for 149 countries. The paper also provides comparisons of the EHII data with measures and estimates from other work. They show that EHII is a reliable reflection of trends, and a reasonable, though not perfect, estimator of the levels of inequality found in surveys.
Keywords: C8; 330; income inequality